Analisis Optimasi Waktu dan Biaya Crashing Project Dengan Metode Critical Path dan Time Cost Trade Off Pada Proyek Pembangunan Galangan Kapal (Studi Kasus PT. Batam Expresindo Shipyard) - Risya Tiara Prasetyawidandi; Renanda Nia Rachmadita; Dian Asa Utari (Proceedings Conference On Design Manufacture Engineering And Its Application, 2022)
The shipbuilding industry is a fabrication industry in the ship sector that involves the use of materials and manufacturing processes.. When a shipbuilding project is finished later than expected, the shipyard is required under the contract agreement to pay a penalty. PT Batam Expresindo Shipyard must pay a penalty equal to 1 mill of the contract value every day because the implementation is delayed, as was the case with the 17M Aluminum Fisheries Supervisory Shipbuilding project.One solution that can be done is by crashing the project on the work that is on the critical path. This research uses Critical Path Method (CPM) and Time Cost Trade Off method. The results of the analysis found that the optimal time and cost with an alternative addition of labor and additional working hours of 5 hours from normal working hours with a productivity of 80%. The resulting crashing project duration is 30 days faster than the actual duration, from a total project duration of 222 days to 192 days with an additional crashing project cost of Rp. 76. 719,846.